Faktor-Faktor Yang Berhubungan Dengan Kejadian Sindrom Koroner Akut Di Ruang Intensif Rumah Sakit Panti Rapih Yogyakarta - Bramasta, Andika; Setya Widyastuti, Chatarina; Marti, Eva (I Care Jurnal Keperawatan STIKes Panti Rapih, 2023)
Background: Acute Coronary Syndrome is an emergency case, especially in coronary arteries, and is the highest cause of death in the world and has even increased in the last 10 years. By knowing the factors associated with the incidence of ACS, it can be used to reduce the incidence of ACS and its complications. Objective: To determine the factors associated with the incidence of acute coronary syndrome in the intensive ward of Panti Rapih Hospital, Yogyakarta. Methods: This research uses descriptive quantitative research with a cross sectional approach. The population of this study were all ACS patients who were treated in the Intensive Room of Panti Rapih Hospital Yogyakarta from January 6 to February 16 2021. The sample in this study was 21 patients with non-probability sampling technique (accidental sampling), data collection using a questionnaire sheet and study documentation. Results: The results showed that smoking (p-value: 1,000), obesity (p-value: 0.334), age (p-value: 0.996), gender (p-value: 0.989) and heredity/family history (p-value: 0.989) value: 0.989) is not related to the incidence of ACS. While the factors associated with ACS are hypertension (p-value: 0.017), diabetes mellitus (p-value: 0.009) and dyslipidemia (p-value: 0.017). Conclusion: Factors associated with the incidence of ACS are hypertension, diabetes mellitus and dyslipidemia. Factors that are not related to the incidence of ACS are smoking, gender and heredity/family history. Keywords: Acute coronary syndrome, risk factors